(untitled) (PerCursos, 2024)
This article aims to discuss points of convergence between Anthropology of the Imaginary, by French anthropologist Gilbert Durand, and the conceptions of Human Ecology. Through a comparative conceptual research (Niz et al., 2016), it was possible to understand that both streams of study have as a point of convergence, the existence of an anthropological trajectory, linked to the biopsychosocial balance of homo sapiens. This perspective offers a complex debate on the relationship between human beings and nature and their diverse habitats, particularly the symbolic habitat. In this sense, this research concludes that it is impossible to dissociate the "ecologicus" being from the "symbolicus" being, as mythical and symbolic narratives are considered essential languages in promoting a poetic and sensitive perspective that translates subjectivity and includes values in the conduct of beings, influencing their worldviews and cultural and socio-environmental practices.